2017
DOI: 10.1088/1755-1315/90/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of exhaust gases and health of the person

Abstract: Abstract. The auto-road complex brings the considerable contribution to pollution and adverse change of environment. Influence of exhaust gases of cars is at the bottom of occurrence and developments of various forms of diseases. Every townsman feels the negative influence rendered by motor transport on himself. The modern city dweller is so accustomed to the smell of exhaust gases that he does not even notice it at all, continues to breathe a poisonous mixture, while neither the car nor the road can be isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…In addition, correlations between episodes of high air pollution and a worsening of allergic and inflammatory conditions of the lung, such as asthma and chronic obstructive pulmonary disease have been clearly evidenced (Miller et al, 2012). However, more recent studies highlighted clear relationships between air pollution and cardiovascular diseases, even claiming that cardiovascular conditions accounted for 40-60% of the premature mortality from air pollution (Beelen et al, 2014;Brunekreef and Holgate, 2002;Dockery et al, 1993;Germanova and Kernozhitskaya, 2017;Greim, 2019;Miller et al, 2012;Miller and Newby, 2020;Shah et al, 2013). Studies also suggested that childhood leukemia and diseases of the nervous system were related to air pollution (Amigou et al, 2011;Germanova and Kernozhitskaya, 2017).…”
Section: Air Pollutionmentioning
confidence: 99%
“…In addition, correlations between episodes of high air pollution and a worsening of allergic and inflammatory conditions of the lung, such as asthma and chronic obstructive pulmonary disease have been clearly evidenced (Miller et al, 2012). However, more recent studies highlighted clear relationships between air pollution and cardiovascular diseases, even claiming that cardiovascular conditions accounted for 40-60% of the premature mortality from air pollution (Beelen et al, 2014;Brunekreef and Holgate, 2002;Dockery et al, 1993;Germanova and Kernozhitskaya, 2017;Greim, 2019;Miller et al, 2012;Miller and Newby, 2020;Shah et al, 2013). Studies also suggested that childhood leukemia and diseases of the nervous system were related to air pollution (Amigou et al, 2011;Germanova and Kernozhitskaya, 2017).…”
Section: Air Pollutionmentioning
confidence: 99%
“…The PrOx-3DOM catalyst presents a well-defined 3DOM structure with high macropores volume, The main pollutants emitted by diesel engines are carbon particles and NOx, together with certain amounts of CO and hydrocarbons [1,2]. These four compounds are responsible, in part, for the air pollution, and there is a set of requirements that regulate the permissible limits for the emissions of combustion gases from these vehicles [3,4]. In recent years, significant efforts…”
Section: Introductionmentioning
confidence: 99%
“…Environmental problems are raised due to the adverse effects of vehicle emissions on human health in urban areas [6][7][8][9][10][11][12], especially for pedestrians and residents living in buildings located near roads. Every year the number of controlled vehicles increases, which leads to serious traffic jams [13][14][15][16], as a result of which a large number of various pollutants are released into the air.…”
Section: Introductionmentioning
confidence: 99%